Determination of Parathion and Carbaryl Pesticides in Water and Food Samples Using a Self Assembled Monolayer /Acetylcholinesterase Electrochemical Biosensor - Mauro Bertotti; Sergio A. S. Machado; Josiane Caetano; Valber A. Pedrosa (Sensors, 2008)
An acetylcholinesterase (AchE) based amperometric biosensor was developed by immobilisation of the enzyme onto a self assembled modified gold electrode. Cyclic voltammetric experiments performed with the SAM-AchE biosensor in phosphate buffer solutions (pH = 7.2) containing acetylthiocholine confirmed the formation of thiocholine and its electrochemical oxidation at Ep = 0.28 V vs Ag/AgCl. An indirect methodology involving the inhibition effect of parathion and carbaryl on the enzymatic reaction was developed and employed to measure both pesticides in spiked natural water and food samples without pre-treatment or pre-concentration steps. Values higher than 91-98.0% in recovery experiments indicated the feasibility of the proposed electroanalytical methodology to quantify both pesticides in water or food samples. HPLC measurements were also performed for comparison and confirmed the values measured amperometrically.